Inner core, asymmetric nash bargaining solutions and competitive payoffs - Sonja Brangewitz; Jan-Philip Gamp (Bielefeld University, Institute of Mathematical Economics (IMW), 2011)
We investigate the relationship between the inner core and asymmetric Nash bargaining solutions for n-person bargaining games with complete information. We show that the set of asymmetric Nash bargaining solutions for different strictly positive vectors of weights coincides with the inner core if all points in the underlying bargaining set are strictly positive. Furthermore, we prove that every bargaining game is a market game. By using the results of Qin (1993) we conclude that for every possible vector of weights of the asymmetric Nash bargaining solution there exists an economy that has this asymmetric Nash bargaining solution as its unique competitive payoff vector. We relate the literature of Trockel (1996, 2005) with the ideas of Qin (1993). Our result can be seen as a market foundation for every asymmetric Nash bargaining solution in analogy to the results on non-cooperative foundations of cooperative games.
Keywords: C71; C78; D51; 330; Inner Core; Asymmetric Nash Bargaining Solution; Competitive Payoffs; Market Games; Verhandlungstheorie; Nash-Gleichgewicht; Core; Marktmechanismus; Wettbewerb; Theorie